Training on Bengawan Solo Water Filtration Techniques in Gampang Sejati Village, Laren Subdistrict, Lamongan Regency - Miftahal Anjarsabda Wira Buana; ZA, Moh. Ah. Subhan; Putri, Marsha Savira Agatha; Artyanto, Sherif Yuniar; Wahyuni, Eka Fita (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
Access to clean water is an essential aspect of a healthy society, as physical and mental well-being cannot be achieved without it. Despite its importance, many water sources are contaminated by household, industrial, and agricultural waste. To address the issue of clean water availability in the region, this community service program aimed to educate and empower residents of Gampang Sejati Village through the implementation of a simple water filtration method using Bengawan Solo River water. The program involved training, socialization, practical application, and evaluation. The primary objective was to equip the community with the knowledge and skills to create and use basic filtration systems that meet health and hygiene standards. A total of 25 community representatives participated in the training sessions, which included technical demonstrations, material introductions, and hands-on practice. Evaluation methods included post-training assessments to measure the effectiveness of knowledge transfer and community feedback. To ensure sustainability, the program proposed forming community groups to oversee the maintenance and improvement of the filtration systems. This initiative aims to provide a long-term solution to water contamination while fostering community responsibility for clean water management. This structured approach not only addressed immediate water filtration needs but also emphasized the importance of continuous education and local engagement for sustainable impacts.